Long-Term Complications in Youth-Onset Type 2 Diabetes - Bjornstad, Petter; Drews, Kimberly L; Caprio, Sonia; Gubitosi-Klug, Rose; Nathan, David M; Tesfaldet, Bereket; Tryggestad, Jeanie; White, Neil H; Zeitler, Philip (The New England journal of medicine, 2021)
A clinical trial assessed the efficacy of three treatments, all involving metformin, on glycemic control in youth-onset type 2 diabetes. This follow-up study shows that the risk of complications increased steadily over time, and complications developed in most participants by young adulthood.